Case report: Abolishing primary resistance to PD-1 blockade by short-term treatment of lenvatinib in a patient with advanced metastatic renal cell carcinoma - Tan, Tingting; Lin, Xiaotong; Ling, Jing; Wang, Rong; Chen, Yue; Cai, Longmei; Sun, Jingyuan; Wu, Dehua; Xie, Guozhu (Frontiers in Immunology, 2023)
Anti-PD-1 immunotherapy has been extensively used in treatment of patients with advanced metastatic renal cell carcinoma (mRCC). Several prospective clinical trials showed that the combined treatment of anti-PD-1 antibody plus lenvatinib, a potent receptor tyrosine kinase inhibitor (TKI), exhibited high response rate compared with single-agent sunitinib. However, whether the patients with primary resistance to PD-1 blockade could benefit from the addition of lenvatinib is still unclear. Herein, we reported a patient with mRCC who was primary resistant to pembrolizumab and achieved a durable complete response after a short-term treatment with lenvatinib. This case report indicates that the patients with primary resistance to anti-PD-1 therapy could benefit from the short-term lenvatinib in combination with anti-PD-1 therapy, and provides a useful paradigm worthy of establishing a clinical trial for mRCC patients with primary resistance to anti-PD-1 therapy.